Routledge handbook of social, economic, and criminal justice - Roberson, Cliff 1937- (Routledge, 2018)
This authoritative volume explores different perspectives on economic and social justice and the challenges presented by and within the criminal justice system. It critically discusses key concerns involved in realizing economic and social justice, including systemic issues in economic and social justice, issues related to organizations and social institutions, special issues regarding specific populations, and a review of national and international organizations that promote economic justice. Addressing more than just the ideology and theory underlying economic and social justice, the book presents chapters with practical examples and research on how economic and social justice might be achieved within the criminal justice systems of the world. With contributions from leading scholars around the globe, this book is an essential reference for scholars with an interest in economic and social justice from a wide range of disciplines, including criminal justice and criminology as well as sociology, social work, public policy, and law
Keywords: Social justice; Economics / Moral and ethical aspects; Distributive justice; Criminal justice, Administration of